On several new results related to Richard's inequality - Conde, Cristian Marcelo (2024)
The main preoccupation of this article is the characterization of Richard’s inequality, which it is closely related to Buzano’s inequality. Finally, we present a new approach for Richard’s inequality, where we use the Selberg operator.